EXPLORING AUTOBIOGRAPHICAL WRITING AS A POTENTIAL FORMATIVE INSTRUMENT FOR PROFESSIONALS WORKING IN PAEDIATRIC WARDS - Gambacorti-Passerini, Maria Benedetta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The specificity of a paediatric ward adds complexity to medical and health practice: providing care, especially to children, invariably involves an educational dimension. Professionals working in paediatric wards are required to deal with such complexity on a daily basis. In this paper I explore the potential of writing, a specific mode of human language, to act as an instrument for helping professionals operating in a paediatric ward to deal with the complexity of their work context. In particular, I assess whether autobiographical writing may be used as an educational training instrument, with a view to designing a course of personal and professional development for professionals in paediatric hospital settings. I focus on the process of reflection stimulated by writing as a source of awareness about how we act in our daily lives and work: such reflection can bring about the desire for change and allow us to find meaning in our individual experience.